Characterization of Hydrogenase II from the Hyperthermophilic Archaeon Pyrococcus furiosus and Assessment of Its Role in Sulfur Reduction - Ma, Kesen (American Society for Microbiology, 2000)
The fermentative hyperthermophile Pyrococcus furiosus contains an NADPH-utilizing, heterotetrameric (αβγδ), cytoplasmic hydrogenase (hydrogenase I) that catalyzes both H(2) production and the reduction of elemental sulfur to H(2)S. Herein is described the purification of a second enzyme of this type, hydrogenase II, from the same organism. Hydrogenase II has an M(r) of 320,000 ± 20,000 and contains four different subunits with M(r)s of 52,000 (α), 39,000 (β), 30,000 (γ), and 24,000 (δ). The heterotetramer contained Ni (0.9 ± 0.1 atom/mol), Fe (21 ± 1.6 atoms/mol), and flavin adenine dinucleotide (FAD) (0.83 ± 0.1 mol/mol). NADPH and NADH were equally efficient as electron donors for H(2) production with K(m) values near 70 μM and k(cat)/K(m) values near 350 min(−1) mM(−1). In contrast to hydrogenase I, hydrogenase II catalyzed the H(2)-dependent reduction of NAD (K(m), 128 μM; k(cat)/K(m), 770 min(−1) mM(−1)). Ferredoxin from P. furiosus was not an efficient electron carrier for either enzyme. Both H(2) and NADPH served as electron donors for the reduction of elemental sulfur (S(0)) and polysulfide by hydrogenase I and hydrogenase II, and both enzymes preferentially reduce polysulfide to sulfide rather than protons to H(2) using NADPH as the electron donor. At least two [4Fe-4S] and one [2Fe-2S] cluster were detected in hydrogenase II by electron paramagnetic resonance spectroscopy, but amino acid sequence analyses indicated a total of five [4Fe-4S] clusters (two in the β subunit and three in the δ subunit) and one [2Fe-2S] cluster (in the γ subunit), as well as two putative nucleotide-binding sites in the γ subunit which are thought to bind FAD and NAD(P)(H). The amino acid sequences of the four subunits of hydrogenase II showed between 55 and 63% similarity to those of hydrogenase I. The two enzymes are present in the cytoplasm at approximately the same concentration. Hydrogenase II may become physiologically relevant at low S(0) concentrations since it has a higher affinity than hydrogenase I for both S(0) and polysulfide.